O uso das TDICs como recurso pedagógico no contexto da pandemia da Covid- 19 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The Covid-19 pandemic caused a significant change in the educational field in the world and in Brazil, due to the social distancing that led schools to use a system called Emergency Remote Teaching (ERE), with the teaching-learning relationship mediated by Technologies Information and Communication Technologies (TDICs). This research uses a qualitative approach and exploratory sequential design. Among the theoretical references, the study of digital culture or cyberculture, the relationship between education and technologies, the field of media education and media literacy stand out. The research theme is “The use of TDICs as a pedagogical resource in the context of the covid-19 pandemic” and the problem “What are the challenges and legacies left by the COVID-19 pandemic in basic education schools regarding the integration of TDICs into the education?". Research articles from the Capes journal base between the years 2020 and 2021 and national surveys carried out by governmental and non-governmental organizations in the same time frame were analyzed. Among the main conclusions of these articles, the following can be highlighted: that research on the subject is concentrated in universities, that the main types of research carried out are qualitative, in terms of objectives, the main reason is to know how the teaching-learning process occurred mediated by technologies in the Covid-19 pandemic, among the main conclusions of the analysis of the articles are that the use of TDICs in the teaching-learning relationship must be a priority in the initial and continued training of teachers in the postpandemic, that teachers must to be open to new methodologies, that the existing inequality in internet access and DICTs among Brazilian students is a reality, either by the type of school they study at, public or private, or by the region where they live. Regarding the national surveys carried out with students from public and private schools, the main conclusions are: internet access is concentrated on cell phones, use for teaching-learning has an inequality of more than 50% between schools in the North and the In the south of Brazil, the use of notebooks is greater in private schools. Among the schools, hybrid teaching stands out as the main teaching mediation strategy through DICTs; less than 50% of schools provided some type of technological equipment for teachers' work, and videoconferencing and messaging applications were the main digital tools used by schools.
Keywords: Mídia-Educação; Práticas educativas; Ensino durante a Covid-19; Educação escolar; TDICs; CNPQ::CIÊNCIAS HUMANAS